Reading for the moral : exemplarity and the Confucian moral imagination in seventeenth-century Chinese short fiction - Sibau, Maria Franca (SUNY series in Chinese philosophy and culture, 2018)
Reassesses didacticism in seventeenth-century Chinese vernacular fiction and challenges the view that the late Ming was a notoriously immoral time.